New American Schools' concept of break the mold designs : how designs evolved and why - Bodilly, Susan J. (Rand, 2001)
Business leaders created New American Schools, a private nonprofit corporation, in 1991 to develop "break-the-mold" designs for schools serving grades K-12. This report documents the significant changes in the designs that have taken place over the initiative's life span and the reasons for those changes. NAS drove some of the changes in its decisions to fund or not to fund specific designs. The designs themselves changed in terms of their educational components and theories. Finally, the design teams developed implementation strategies and assistance packages over time that resulted in the expansion of the design concept to the concept of "design-based assistance." Some of the changes made to designs were beneficial in promoting the concept of a design-based school, especially the development of stronger curriculum packages, clearer descriptions of the designs, and significant work toward assistance for schools to adopt designs. However, concessions to district and state policies led design teams to redefine some design elements, allowing significant local variation and possible incoherence and fragmentation within schools using designs. If this reform is to succeed, policymakers must revitalize it by taking the current environment into account and helping to make it more supportive